Compaction of LiBH4-LiAlH4 nanoconfined in activated carbon nanofibers: Dehydrogenation kinetics, reversibility, and mechanical stability during cycling. (12th January 2017) - Plerdsranoy, Praphatsorn; Javadian, Payam; Jensen, Nicholai Daugaard; Nielsen, Ulla Gro; Jensen, Torben René; Utke, Rapee
Abstract: To enhance volumetric hydrogen capacity for on-board fuel cells, compaction of LiAlH4 -LiBH4 nanoconfined in activated carbon nanofibers (ACNF) is for the first time proposed. Loose powders of milled and nanoconfined LiAlH4 -LiBH4 samples are compacted under 976 MPa to obtain the pellet samples with thickness and diameter of ∼1.20–1.30 and 8.0 mm, respectively. Dehydrogenation temperature of milled LiAlH4 -LiBH4 increases from 415 to 434 °C due to compaction, while those of both compacted and loose powder samples of nanoconfined LiAlH4 -LiBH4 are lower at comparable temperature of 330–335 °C. Hydrogen content liberated from milled LiAlH4 -LiBH4 pellet is 65% of theoretical capacity in the temperature range of 80–475 °C, while that of nanoconfined LiAlH4 -LiBH4 pellet is up to 80% at lower temperature of 100–400 °C. Besides, nanoconfined LiAlH4 -LiBH4 pellet shows significant reduction of activation energy (Δ E A up to 69 kJ/mol H2 ) as compared with milled sample. Significant enhancement of volumetric hydrogen storage capacity up to 64% (from 32.5 to 53.3 gH2 /L) is obtained from nanoconfined LiAlH4 -LiBH4 pellet. Hydrogen content released and reproduced of nanoconfined LiAlH4 -LiBH4 pellet are 67 and 50% of theoretical capacity, respectively, while those of milled LiAlH4 -LiBH4 pellet are only 30 and 10%, respectively. Moreover, upon four hydrogen release and uptake cycles, nanoconfined LiAlH4 -LiBH4 pellet can preserve its shape with slight cracks, suggesting good mechanical stability during cycling. Curvatures and fibrous structure woven on one another of ACNF in nanoconfined LiAlH4 -LiBH4 pellet not only favor hydrogen permeability through pellet sample during de/rehydrogenation, resulting fast kinetics, but also reinforce the pellet shape during cycling under high temperature and pressure condition. Highlights: First time compaction of nanoconfined LiAlH4 LiBH4 in pellet form under 976 MPa. Comparable dehydrogenation temperature (330–335 °C) with loose powder. Lowered E A and desorption temperature by 69 kJ/mol H2 and 85 °C, respectively. Greater volumetric H2 capacity up to 64% than pellet of milled sample. Good mechanical stability during cycling and H2 permeability through the pellet.